REFORMASI PENDIDIKAN KEWARGANEGARAAN DAN TRANSFORMASI SUBYEKTIFITAS DALAM ERA GLOBALISASI - Gjelstad, Lars E. (PKn Progresif, 2008)
This paper aims to put civics education into historical perspective and the wider political. Civic education related to the globalization of market capitalism (market capitalism), which also leads to the emergence of cultural values of the new, which is not always explicit, but more implicitly into the model of education and new development. One important aspect of this change is a radical transformation of subjectivity among the new generation of Indonesian students. Major task of citizenship education is to assist in understanding the process not only cultural but also historical contexts. His statement is whether the competency-based curriculum of civic education can engage students in discussion about what it means to be a good citizen of Indonesia in the 21st century.